Citrulline – The Powerhouse Nutrient for Cardiometabolic and Brain Health - Daria Pedrycz; Mateusz Drabczyk; Emilia Pedrycz; Karolina Karoń; Grzegorz Drapała; Wojciech Grabowski; Łukasz Karoń; Anna Zygmunt; Sławomir Karoń (Quality in Sport)
Citrulline, a non-essential amino acid and precursor to L-arginine, plays a pivotal role in nitric oxide (NO) synthesis, with profound implications for vascular health and neuroprotection. By enhancing NO production, citrulline supports endothelial function, vasodilation, and cerebral circulation, thereby mitigating cognitive decline associated with aging and neurodegenerative diseases. Unlike direct arginine supplementation, citrulline offers superior bioavailability, bypassing first-pass metabolism and achieving sustained plasma levels of arginine. Furthermore, citrulline's antioxidant properties counteract oxidative stress by modulating reactive oxygen species (ROS), reducing lipid peroxidation, and protecting neuronal integrity. Emerging evidence suggests its potential in delaying endothelial senescence and preventing ferroptosis, establishing its role in vascular and neuroprotective strategies. Dietary sources, such as watermelon juice, further enhance citrulline’s accessibility, combining its bioactivity with additional antioxidants like lycopene. While existing studies underscore its promise, targeted research is needed to confirm its direct impact on cognitive function and explore its application in neurodegenerative populations. This review synthesizes current knowledge on citrulline's mechanisms, therapeutic potential, and broader implications for aging and vascular health.